Tingkat Pendidikan Dan Masa Kerja Terhadap Kinerja Karyawan Pt Prima Makmur Rotokemindo - Yudha Supriyatna (Universitas Serang Raya, 2020)
This study aims to determine the effect of education level and tenure on the performance of PT Prima Makmur Rotokemindon employees. In this study using a quantitative approach with study data collection techniques to distribute questionnaires to respondents. The selected sample is 71 people. And the object used in this study is employees at PT Prima Makmur Rotokemindo while the objects in this study are the level of education, years of service, and employee performance. Data were analyzed by multiple regression analysis with SPSS 23.0 for Windows which included t test and F test. The results of this study were: (1) The level of education had a significant effect on the performance of PT Prima Makmur rotokemindo employees. (2) The period of work has a significant effect on the Employee Performance of PT Prima Makmur Rotokemindo. (3) The level of education and working period simultaneously have a significant effect on the performance of PT Prima Makmur Rotokemindo.Keywords: Level of Education, Employee Work Period, and Employee Performance